PENENTUAN BENTUK DAN UKURAN PLOT CONTOH OPTIMAL PENGUKURAN KEANEKARAGAMAN SPESIES TUMBUHAN DI HUTAN PEGUNUNGAN BAWAH - M. Adlan Ali; Agus Hikmat; Yanto Santosa (Department of Forest Resources Conservation and Ecotourism - IPB University, 2016)
Several recent books have focused on the importance of biological diversity but none contain precise methodologies to measure it. The purpose of this study is to determine the shape and size optimal sampling plot to measure the plant species diversity in highland tropical rain forest base in a case study on the Betung Kerihun National Park (TNBK). Data were collected in the TNBK, Kapuas Hulu Regency , East Kalimantan on July till August 2015. The data collection was carried out by making five shape sampling plot such as rectangle and square with different size. Variables collected are the number of individuals species of plant from seedlings, saplings, poles, and trees. Data were analyzed using Annnova test and least significance difference (BNT). The result showed that the total species richness observed on squares and rectangles plot respectively 306 , 761 , 142 , 265 , and 156 species of plants with the dominant are Dipterocarpaceae Family. The optimal dimensions plot for measurement the plant diversity are rectangular shape with dimensions of length adhering the contour with a size 50x200 m2.Keywords: dimensions,optimal plot, shape, species richness